Cloning of an Erwinia herbicola gene necessary for gluconic acid production and enhanced mineral phosphate solubilization in Escherichia coli HB101: nucleotide sequence and probable involvement in biosynthesis of the coenzyme pyrroloquinoline quinone. - Liu, S T (1992)
Escherichia coli is capable of synthesizing the apo-glucose dehydrogenase enzyme (GDH) but not the cofactor pyrroloquinoline quinone (PQQ), which is essential for formation of the holoenzyme. Therefore, in the absence of exogenous PQQ, E. coli does not produce gluconic acid. Evidence is presented to show that the expression of an Erwinia herbicola gene in E. coli HB101(pMCG898) resulted in the production of gluconic acid, which, in turn, implied PQQ biosynthesis. Transposon mutagenesis showed that the essential gene or locus was within a 1.8-kb region of a 4.5-kb insert of the plasmid pMCG898. This 1.8-kb region contained only one apparent open reading frame. In this paper, we present the nucleotide sequence of this open reading frame, a 1,134-bp DNA fragment coding for a protein with an M(r) of 42,160. The deduced sequence of this protein had a high degree of homology with that of gene III (M(r), 43,600) of a PQQ synthase gene complex from Acinetobacter calcoaceticus previously identified by Goosen et al. (J. Bacteriol. 171:447-455, 1989). In minicell analysis, pMCG898 encoded a protein with an M(r) of 41,000. These data indicate that E. coli HB101(pMCG898) produced the GDH-PQQ holoenzyme, which, in turn, catalyzed the oxidation of glucose to gluconic acid in the periplasmic space. As a result of the gluconic acid production, E. coli HB101(pMCG898) showed an enhanced mineral phosphate-solubilizing phenotype due to acid dissolution of the hydroxyapatite substrate.